القطع في أصول فقه الأمامية (مقارنا بأصول فقه أهل السنة) - البرزنجي, صباح محمد نجيب (Sulaimani Journal for Humanities, 2000)
The assurance in Al Emamia approach The science of the jurisprudence rules is a fundamental science to understand the Islamic law, SO. The Islamic scientists followed different approaches to record this science, among the important approach is the approach of theologian, which is considered a mental and deductive approach and started with Abu-Alhusain Al - Basrees' Writings, Al-Juwainee and Al Ghazzalee. This approach ( the theology approech ) attracted the attention of all the jurisprudence approech as Al Emamia or Al Sheia approech who were affected grently by Al Sunna in the science of jurisprudence rules for along time. Lately invented a new approech , which flourished by Shaikh Murtadha Al Ansari writings who invented a new way in this science, and divided the sections of this science into all the inner cousciouness through which the assidions passes : these states are assurance, suspicion and doubt. This article shed the light on (assurance) subject in Al Sheia jurisprudence comparatively with Al Sunna jurisprudence and shows similarities and differences between the tow. This is consirered as important trial to near the muslims of rifferent approaches.